Problem solving: a diagnosis of Mathematics teaching in the Final Grades of Elementary (Research, Society and Development, 2022)
Throughout human history, the teaching of mathematics was surrounded by countless fears and mysticisms around the discipline. Students are sometimes afraid of learning about this subject. For this scenario starts to change, researches are being developed about the teaching of Mathematics, among them, the Problem-Solving Methodology stands out. This tool seeks to enable the student to mobilize knowledge and later develop skills to manage and process knowledge so that information can be better absorbed. The present work aimed to understand the definition of Problem Solving in the teaching of mathematics in the final years of elementary school. A literature review was carried out to understand how the concepts related to this article are perceived. It was concluded with the study that the Problem-Solving Methodology presents itself as an important tool in the learning process in mathematics teaching.